Implementation of the Game Development Life Cycle for an Android-based Color Theory Educational Game - Raditya Wardhana; Muhammad Tofa Nurcholis; Buyut Khoirul Umri (Universitas Islam Indragiri, 2026)
Students often experience difficulties in understanding color theory, particularly when it is taught through conventional theoretical instruction without interactive or visual learning support. Although they pay attention to the instructional content, approximately 65% of students still struggle to apply color theory concepts in graphic design. This study aims to develop an Android-based educational game to facilitate students' understanding of color theory through an interactive and visual learning experience. The game was developed using the Game Development Life Cycle (GDLC), which consists of six phases: initiation, pre-production, production, testing, beta, and release. Construct 2 was used as the game development platform. The game incorporates two-dimensional animations covering key topics, including color theory, color meanings, color temperature, color dimensions, and color schemes. The learning materials are presented through engaging visual storytelling to enhance comprehension. The game was evaluated through alpha and beta testing, while user responses were assessed using a Likert-scale questionnaire. The evaluation results indicate that the game is functional, engaging, enjoyable, and effective in delivering educational content. Therefore, the proposed educational game provides an alternative and interactive approach to teaching color theory to students.